Different immunological mechanisms between AQP4 antibody-positive and MOG antibody-positive optic neuritis based on RNA sequencing analysis of whole blood - Chen, Xuelian; Cheng, Libo; Pan, Ying; Chen, Peng; Luo, Yidan; Li, Shiyi; Zou, Wenjun; Wang, Ke (Frontiers in Immunology, 2023)
Purpose: To compare the different immunological mechanisms between aquaporin 4 antibody-associated optic neuritis (AQP4-ON) and myelin oligodendrocyte glycoprotein antibody-associated optic neuritis (MOG-ON) based on RNA sequencing (RNA-seq) of whole blood. Methods: Whole blood was collected from seven healthy volunteers, 6 patients with AQP4-ON and 8 patients with MOG-ON, and used for RNA-seq analysis. An examination of immune cell infiltration was performed using the CIBERSORTx algorithm to identify infiltrated immune cells. Results: RNA-seq analysis showed that the inflammatory signaling was mainly activated by TLR2, TLR5, TLR8 and TLR10 in AQP4-ON patients, while which was mainly activated by TLR1, TLR2, TLR4, TLR5 and TLR8 in MOG-ON patients. Biological function identification of differentially expressed genes (DEGs) based on Gene Ontology (GO) term and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis, as well as Disease Ontology (DO) analysis, showed that the inflammation in AQP4-ON was likely mediated by damage-associated molecular pattern (DAMP), while which in MOG-ON was likely mediated by pathogen-associated molecular pattern (PAMP). Analysis of immune cell infiltration showed that the proportion of immune cell infiltration was related to patients' vision. The infiltration ratios of monocytes (rs=0.69, P=0.006) and M0 macrophages (rs=0.66, P=0.01) were positively correlated with the BCVA (LogMAR), and the infiltration ratio of neutrophils was negatively correlated with the BCVA (LogMAR) (rs=0.65, P=0.01). Conclusion: This study reveals different immunological mechanisms between AQP4-ON and MOG-ON based on transcriptomics analysis of patients’ whole blood, which may expand the current knowledge regarding optic neuritis.